1. Distribute the negative (-) to what’s inside the parentheses. *Keep in mind that a negative times a negative is a positive.*
➡️ -2y+2=-7+4-1
2. Combine like-terms. In this case, the right side of the equation contains like-terms, which are the constants (numbers).
➡️ -2y+2=-4
3. Get the constants to one side of the equation. You will do this by subtracting +2 by its opposite, -2, to -4.
➡️ -2y = -6
4. Your last step is to divide -2 on both sides of the equal sign to cancel out y’s coefficient.
➡️ -2y/-2 = -6/-2
* Because dividing a negative by a negative equals a positive, your answer will be y = 3.